2012
DOI: 10.1073/pnas.1209508109
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling in facioscapulohumeral muscular dystrophy to identify candidate biomarkers

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is a progressive neuromuscular disorder caused by contractions of repetitive elements within the macrosatellite D4Z4 on chromosome 4q35. The pathophysiology of FSHD is unknown and, as a result, there is currently no effective treatment available for this disease. To better understand the pathophysiology of FSHD and develop mRNA-based biomarkers of affected muscles, we compared global analysis of gene expression in two distinct muscles obtained from a large number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 49 publications
5
101
1
Order By: Relevance
“…Due to the complexity of SORBS2 (42 exons, 118 putative transcripts), previous results are often contradictory, with some observing up-regulation (Celegato et al 2006), and others reporting no change in the expression of this gene (Masny et al 2010;Rahimov et al 2012). These results are not surprising if the major changes involve modifications of the splicing pattern rather than a global change in the transcription level.…”
Section: Sorbs2 Is Activated By Tpe-old In Fshd Myoblastcontrasting
confidence: 41%
“…Due to the complexity of SORBS2 (42 exons, 118 putative transcripts), previous results are often contradictory, with some observing up-regulation (Celegato et al 2006), and others reporting no change in the expression of this gene (Masny et al 2010;Rahimov et al 2012). These results are not surprising if the major changes involve modifications of the splicing pattern rather than a global change in the transcription level.…”
Section: Sorbs2 Is Activated By Tpe-old In Fshd Myoblastcontrasting
confidence: 41%
“…Actin cytoskeleletal signalling has also been implicated in FSHD pathology [15]. Our work shows perturbed crosstalk between such signalling and HIF1-a may contribute to FSHD.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, it was recently demonstrated that DUX4 drives over half the differentially expressed transcripts in FSHD [18]. However, the number of differentially expressed transcripts is very low in FSHD as compared with other pathologies [18,5,15] and it has been shown that a more subtle transcriptional dysregulation may better represent unifying features of FSHD [15]. Our FSHD network captures such subtle dysregulation and it was important to determine whether the network, derived from unbiased meta-analysis of multiple muscle biopsies from FSHD patients, could be controlled by DUX4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluidigm, for example, provides high-throughput real-time quantitative PCR based on proprietary microfluidic chips (Rahimov et al 2012). These gene expression assays are commercially available, but they are still costly and require specialized equipment not routinely available in laboratories in most TB-endemic areas.…”
Section: Focused Transcriptomic Approaches To Identify Tb Biomarkers mentioning
confidence: 99%